Scenarios of Development of Metropolitan City Housing Market Based on the Example of Cracow - Lityński, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the article is to identify future trends in the housing market of a developing metropolitan city. The recognition of these tendencies is crucial for the course of economic development processes in the country. Housing plays an important role in social, economic and spatial development. In empirical studies, three scenarios have been adopted for the development of the housing market. As an example, the City of Cracow, which is the second largest city in Poland with a dynamically developing economy, was chosen. Among the important conclusions is the conclusion that the pro‑supply housing activity of the national government can have a lesser impact on the development of the metropolitan housing market than the losses caused by governmental activity in areas outside the building sector (e.g.: the reform of higher education) which reduces demand for housing. Extrapolation methods were used in the conducted analyses and CSO as well as external reports served as data sources.